Psychiatric Disorder in Renal Patients - Andri (ANIMA Indonesian Psychological Journal, 2013)
Patients with chronic kidney failure are one of the most complex conditions in the practice of consultation-liaison psychiatry (CLP). This is due to the long course of the disease and treatment. It is also related to the complications of the kidney failure that often appear to make patients helpless dealing with it. One of the complications of kidney failure is mental disorder symptoms. This paper presents three cases of chronic kidney failure that had psychiatric disorder which were common experienced by chronic kidney failure patients: delirium, depression, and disequilibrium syndrome. Each case has a background of a different physiology and psychopathology. The handling of cases with psychiatric disorder in patients with chronic kidney failure were adjusted to patient’s general medical condition and psychopathology. Pasien dengan gagal ginjal kronis adalah salah satu kondisi pasien yang paling kompleks dalam praktek psikiatri konsultasi liaison. Hal ini disebabkan karena perjalanan penyakit yang panjang dan komplikasi yang sering muncul membuat pasien sering tidak berdaya menghadapi penyakit. Selain itu gagal ginjal kronis sendiri sering membawa komplikasi dalam bentuk gejala gangguan jiwa. Tulisan ini mengemukakan tiga kasus pasien gagal ginjal kronis yang mempunyai komplikasi gangguan jiwa yang paling sering dialami pasien yaitu; delirium, depresi dan sindrom disequilibrium. Masing-masing kasus mempunyai latar belakang fisiologi dan psikopatologi yang berbeda. Penanganan kasus-kasus gangguan kejiwaan pada pasien gagal ginjal kronis disesuaikan dengan kondisi medis umum pasien dan psikopatologinya.